O Direito Tributário através dos olhos dos despossuídos: por uma crítica dos fundamentos morais da ideia de contribuinte na teoria do Direito Tributário - Thiago Alvares Feital (2017)
A critical legal theory about the subject of taxation still hasnt been developed in Brazil. Therefore, the literature is permeated by arguments derived from common sense, inspired by a neoliberal conception of the subject, which produces legal effects: the dispossessed, who sees themselves as not protected by Tax Law, are made invisible, and the National Tax System is revealed as opaque to these people. Despite the gravity of those effects, they are not discussed in most of Tax Law literature. This points to a detachment between Tax Law research under the 1988 Brazilian Constitution and the countrys socio-political reality. This thesis intends to identify how the Brazilian Tax Law makes the dispossessed invisible, considering the National Tax Systems regressivity and the absence of further discussions in the most renowned Tax Law books and articles about this issue. It also seeks to show that this exclusion of the dispossessed is related to higher courts decisions about recovery of undue payments of indirect taxes; de facto taxpayers exclusion from Taxpayers Bill of Rights in force; and the validation of Brazilian value aggregate tax imposition on a base that includes the tax itself. In order to do so, an overview of equity theories in Tax Law is presented, to reveal the proximity of economic theories and Tax Law. Afterwards, the dispossessed position in the National Tax System is evidenced. This thesis indicates to principle of solidaritys potential to reformulate the taxpayer concept and to change the meaning of responsibility in this context. Both solutions constitute requirements to the development of a democratic Tax Law.